PEMUNGUTAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN PADA BADAN PENGELOLAAN KEUANGAN KOTA BANDA ACEH (STUDI IMPLEMENTASI KEBIJAKAN QANUN KOTA BANDA ACEH NO. 12 TAHUN 2011 TENTANG PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN) - Nanda Rizkia Rahila (Jurnal Transformasi Administrasi, 2021)
In realizing a comprehensive autonomous region, Aceh as an autonomous region must be able to manage sources of income sourced from the Rural and Urban Land and Building Tax (PBB-P2). This study aims to find out how the collection and management of PBB-P2 carried out by the City Financial Management Agency (BPKK) of Banda Aceh, can increase the Regional Original Income (PAD) of Banda Aceh City. The methodology used in this study is a descriptive qualitative method, focusing on finding facts that describe behavior, events, with the aim of describing a variable related to the focus and problem under study. The results of the study indicate that there are still obstacles in the collection and management process, such as the need for foresight of collecting officers in recording taxpayers' data (WP), determining the amount of PBB-P2 that must be paid by taxpayers, and understanding of taxpayers in order to comply with their obligations. The conclusion of this study explains that there is a need for a systematic interrelated collection and management process to facilitate the collection and management of PBB-P2 so that with increasing income from PBB-P2, PAD income also increases so that government, development and social activities can run well.